SINGLE VESUS MULTIPLE SOURCE PURCHASING STRATEGY - Khai Sheang Lee; Hean Tat Keh; Tuck Siong Chung (Asian Academy of Management Journal, 2000)
In this paper, we look at the choice between a single and a multiple source purchasing strategy. Using a game theoretic approach, we examine the impact of the economies of scale and specific knowledge on the choice of sourcing strategy, explicitly taking into account the small numbers interactions involving a buyer and two competing suppliers. We show that economies of scale and specific knowledge have opposing effects on sourcing strategies. While a single source strategy is favored when efficiency gains due to economies of scale are large, a multiple source strategy is the dominant strategy in the long run when specific knowledge acquired by a supplier becomes substantial. In following a multiple source strategy, it is also optimal for a buyer to split the supply contract symmetrically across the suppliers, in order to appropriate all efficiency gains that result from the acquisition of specific knowledge by its suppliers. However. splitting of the supply contract results in a reduction in gains due to the economies of scale.